2021
DOI: 10.1002/jbt.22829
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the biomechanistic role of Rac1/TWEAK/Fn14/NF‐κB intricate network in experimentally doxorubicin‐induced cardiotoxicity in rats: The role of curcumin

Abstract: Doxorubicin (DOX) is an important chemotherapeutic drug. Cardiotoxicity diminishes its clinical efficacy. We aimed to focus on the mechanism of DOX‐induced cardiotoxicity, in addition, to evaluate curcumin's protective effect against it. Twenty‐eight rats were divided into the normal control group I, curcumin‐treated (200 mg/kg body weight [b.w.]) group II, DOX‐treated (4 mg/kg b.w.) group III, and DOX + curcumin group IV. Cardiac injury markers, heart tissue oxidative stress indices, interferon‐gamma (INF‐γ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The results showed that SPM had a dual effect by promoting both P53 expression and phosphorylation, while simultaneously inhibiting Rac1, thereby reversing the effect of SPM on P53 expression and phosphorylation. These results suggest that P53 is a potential downstream molecule of Rac1, with SPM promoting the expression of both, consistent with previous researches ( Mishra et al, 2019 ; Soliman et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that SPM had a dual effect by promoting both P53 expression and phosphorylation, while simultaneously inhibiting Rac1, thereby reversing the effect of SPM on P53 expression and phosphorylation. These results suggest that P53 is a potential downstream molecule of Rac1, with SPM promoting the expression of both, consistent with previous researches ( Mishra et al, 2019 ; Soliman et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, CUR (below 50 μM) treatment induces p53/p21-dependent apoptosis and significantly inhibits SH-SY5Y cell growth and migration [ 151 ]. An in vitro study showed that CUR treatment (200 mg/kg/day, gavage) can significantly downregulate the expression of genes such as Rac1 and p53 in myocardial tissue, highlighting a potential application of CUR in the prevention of DIC [ 152 ]. Meanwhile, RES, an anthraquinone terpenoid that is highly abundant in grapes, was first reported to have an anticancer effect in 1997 [ 153 ].…”
Section: Nutrients Can Attenuate Dox Toxicity and Drug Resistance By ...mentioning
confidence: 99%
“…Ten different non-overlapping randomly selected fields from each section were examined at a magnification of 400 to quantitatively evaluate the mean colour intensity of Bax, Bcl-2 and NFκB positive immunohistochemistry reaction. The colour intensity was calculated by subtracting the colour intensity of negative immunohistochemistry control from the colour intensity of positively stained specimens in serial sections while eliminating the background (Soliman et al, 2021).…”
Section: Immunohistochemistry Quantitative Assessmentmentioning
confidence: 99%